Graphic design for art, fashion, film, architecture, <U+000d><U+000a>photography, product design & everything in betwee - Cooke, Andy, 1986; Lewis, Angharad (M<U+00fc>nchen: Prestel Verlag, 2018)
This book explores ways in which graphic designers can successfully collaborate with other creative professionals and sectors, whether it be a more sophisticated logo for a product, a better-designed lookbook for a fashion brand, or a more intuitive wayfinding system for a museum. It features exceptionally conceived design solutions across a variety of industries, from architecture and product <U+000d><U+000a>design to art, fashion, and film. Each example illustrates the significance of the graphic designer's role in making a campaign marketable and successful, and insights from clients and the designers themselves reveal the inner workings of the design process. The result is an indispensable reference for the graphic design industry that shows how excellence can be achieved when creative minds work together
Keywords: Graphic arts; Commercial art; Visual communication